ANALYSIS THE EFFECT OF GOOD GOVERNANCE, SUPERLEADERSHIP, ORGANIZATIONAL CULTURE ON WORK MOTIVATION AND WORK SATISFACTION: (Study on the Industry and Trade Office of Blitar Regency) - Suci Ayu Ambarwati; Indria Guntarayana (Universitas Islam Balitar, 2019)
Job satisfaction and work motivation of employee certainly cannot emerge by itself; it can be influenced by many factors. One of them is leadership, therefore this study was independent conducted with the aim of knowing and explaining the relationship and the influence of variables namely Good Governance, Super leadership, Organizational Culture on Work Motivation and Job Satisfaction. This study uses a mixed strategy method of Smart PLS and qualitative SEM analysis tools in the derming cycle model, especially the concurrent triangulation strategy as collecting qualitative data at the same time at the research stage, then comparing qualitative data with quantitative data to determine differences in combinations. After analysis, the results achieved in this research indicate that 1) Organizational Culture influences Job Satisfaction. 2) Organizational culture has no effect on work motivation. 3) Good Governance does not effect on Job Satisfaction. 4) Good Governance influences Work Motivation. 5) Work Motivation influences Job Satisfaction. 6) Super leadership has no effect on Job Satisfaction. 7) Super leadership does not effect on Work Motivation. From this analysis the suggested implication strategies that can be used to create employee satisfaction and motivation are to provide excellent service to work partners, revitalization or market development in each region. Conduct employee training